26=7(j-9)+12

Simple and best practice solution for 26=7(j-9)+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=7(j-9)+12 equation:



26=7(j-9)+12
We move all terms to the left:
26-(7(j-9)+12)=0
We calculate terms in parentheses: -(7(j-9)+12), so:
7(j-9)+12
We multiply parentheses
7j-63+12
We add all the numbers together, and all the variables
7j-51
Back to the equation:
-(7j-51)
We get rid of parentheses
-7j+51+26=0
We add all the numbers together, and all the variables
-7j+77=0
We move all terms containing j to the left, all other terms to the right
-7j=-77
j=-77/-7
j=+11

See similar equations:

| -5x-16=9x+9-1 | | x2-4x-13=0 | | -528=22z | | 3x-15=2x-10-1x | | 11j=319 | | 9x+8)+(10x)+(8x+10)=180 | | 4x-3(6)=6-12 | | n=n+345 | | 25=4n−3 | | 8x-3=-16 | | -3(y/3+1)-2=4(1-y) | | v+-154=588 | | 4(-3)+7y=2 | | 18d-17d=13 | | –r-5=1–2r | | 8x+6=25 | | v+47=82 | | 4a+6=8a-6 | | 15/2x=6/x+9 | | h=6h+15 | | 2(x−4)(x+1)=0 | | -8x-4=4-5x | | X-0.12x=185 | | j+242=708 | | 5x+8(85-x)=500 | | (3x+x)/2=486 | | 4x+24-8×=2x | | 11x-6+134=180 | | c-9=62 | | 12x-(x+5)=10x-1 | | 3+^x-6=^x+9 | | 3y+2(y-4)=5(y-1)+2y+3 |

Equations solver categories